2023
DOI: 10.2174/1570193x20666221018090845
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloids as Antimalarial Compounds: A Review of Recent Studies

Abstract: Malaria is a parasitic infection caused by Plasmodium parasites that are transmitted to humans through the bite of infected Anopheles mosquitoes. Malaria continues to contribute unacceptably high rates of sickness and death. Natural product compounds have long been recognized as one of the valuable natural remedy resources with promising structural motif pools for the development of first-line drugs. Resistance to conventional treatments such as chloroquine, mefloquine, and artemisinin-based combination therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Although artemisinin did show good therapeutic effects, it has some drawbacks such as low solubility (the solubility in water was as low as 0.059 mg/mL), poor bioavailability (approximately 30%), and short half-life time (2–3 h). In order to solve these problems, new types of antimalaria APIs and various derivatives of artemisinin, like artesunate (ART) and dihydroartemisinin (DHA), were developed; a series of finely designed nanovesicles have been proposed to efficiently deliver artemisinin as well as its derivatives. , For instance, Gao et al proposed a self-emulsifying drug delivery system (SEDDS), which displayed higher solubility, permeability, and bioactivity . Since artemisinin is of low molecular weight and displays obvious hydrophobicity (log P = 2), transdermal delivery may be an efficient way, which shows a lot of merits that can promote the bioavailability and convenience. , However, only a few research studies concerning the transdermal delivery of artemisinin have been reported, where solid dispersions, microemulsions, solid lipid nanoparticles (SLNs), niosomes, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Although artemisinin did show good therapeutic effects, it has some drawbacks such as low solubility (the solubility in water was as low as 0.059 mg/mL), poor bioavailability (approximately 30%), and short half-life time (2–3 h). In order to solve these problems, new types of antimalaria APIs and various derivatives of artemisinin, like artesunate (ART) and dihydroartemisinin (DHA), were developed; a series of finely designed nanovesicles have been proposed to efficiently deliver artemisinin as well as its derivatives. , For instance, Gao et al proposed a self-emulsifying drug delivery system (SEDDS), which displayed higher solubility, permeability, and bioactivity . Since artemisinin is of low molecular weight and displays obvious hydrophobicity (log P = 2), transdermal delivery may be an efficient way, which shows a lot of merits that can promote the bioavailability and convenience. , However, only a few research studies concerning the transdermal delivery of artemisinin have been reported, where solid dispersions, microemulsions, solid lipid nanoparticles (SLNs), niosomes, etc.…”
Section: Introductionmentioning
confidence: 99%